Konstitusi Desa dan Eksistensinya dalam Regulasi di Indonesia - Marthen B. Salinding (The Constitutional Court of the Republic of Indonesia, 2021)
Herman Heller means that the constitution has 3 (three) phases: the constitution as a reality; the constitution in the abstraction process; and the constitution in codification. A constitution that has passed through the codification cycle is a mirror that it has found its existence and its position as a reality of socio-political life in society, or at least the constitution can describe the concept of Fundamental of a country’s community-thinking society. To interpret the understanding, the context of the Constituent Assembly as an abstraction of the value of dynamic living in the community (law and change of society), especially the village community in the period of reform that has undergone significant shifts because of abstraction errors on the constitution. Positioning the village as one of the sub-systems governance that has existed during the state of the archipelago (before Indonesia), the village has positioned the constitution at that time without passing the abstraction to codification. Thus the form of the constitution as the law contained therein rests on the provisions of the Godhead (natural law) far from the conception of value built on the rationality schemes and regulatory logic. Through normative juridical research methods and 3 (three) approaches: Historical approach, conceptual approach, and statue approach, the purpose of this research is to trace the significance of the village constitution as a unity of the village society’s reality by analyzing the context of historical and the things that are behind the trend of the conception of village society before the constitution passed the codification phase and the existence of the village constitution itself in regulations reflected in the law of the Republic of Indonesia number 6 the year 2014 about the village.